Use of biopanels in bagasse - derived ceilings for thermal comfort in homes in the sierra - altoandina, Aramachay, Jauja - Baltazar Ramos, Aida Diana (2025)
The research evaluates the effectiveness of bagasse as a residual organic material and its implementation as a roofing solution for housing in high Andean areas, knowing and interpreting the circumstances of the Aramachay - Jauja annex, from the climatological issue to the economic status of the local population. The methodology was experimental; quantitative and qualitative data were collected, to address figures such as thermal levels, in addition to the results of the instruments (anemometer and thermo hygrometer) to measure the temperature and humidity throughout the experimental part; on the other hand, qualitative information was handled slime and paste; in spite of highlighting more, the desired thermal comfort index was not reached. We can affirm that the use of heat regulating systems such as the trombe wall or the covering proposed in this article does not cover the thermal comfort degrees due to its isolated and individual use, but if a housing design that considers all these unified elements is taken into account, it would clearly have a better response; besides, it would remain as a tentative precedent in social housing in high Andean zones. based on surveys and interviews with the residents of the annex to better interpret their feelings and context, in addition to obtaining relevant data such as their economy. A diagnosis of the environment and analysis of materials are contemplated; from these, we will know the different problems, effects and thermal needs inside the houses that the settlers are facing, in addition to the properties of the materials that will serve as conglomerating elements with the bagasse, cement, gypsum, paste and sugarcane slime were considered. Afterwards, the results of the feasibility of the resulting mixtures are evaluated, in addition to their implementation in a modular space and finally, the temperature and humidity figures are taken every three hours in the span of a whole day (24 hours). It was determined that the biopanels used as covers provide a slight thermal degree to the interior of the module and the mixture with the best favorable effect was bagasse, stalk